Perfil clínico e epidemiológico das pacientes do ambulatório de mola da Fundação Santa Casa De Misericórdia Do Pará de fevereiro de 1996 a janeiro de 2004 em seus 8 anos de serviço - CORRÊA, Alessandra Costa (2022)
Gestational trophoblastic disease is a generic term that assigns pathologies originated from the covering fabric of the chorionic villi (citotrophoblastic end sinciciotrophoblastic). Constituting this group, Hydatiform Mole, Invasive Mole or Corioadenoma Destruens, Choriocarcinoma and Trophoblastic tumor are placentary included. The hydatifoem mole represents the benign form of the illness, whereas excessively they condtitute the gestational trophoblastic tumors, susceptive to produce metastasis and to lead to the death. This work is retrospective being that 646 handbooks of patients with DTG diagnosis had been enclosed. The population was composed from womens whose age of bigger incidence was between 16 and 25 years, residents in Belém and metropolitan region, pregnance first and pregnance second, never parity and that they had never aborted. The genital hemorrhage and uterus increased for gestational age had been the symptoms most frequent. And the presented time of evolution of the illness were between 11-20 weeks . The dilatation and curettage were the most used method to uterine evacuation. And the most common complication was uterine hemorrhage. The preferred contraceptive method was the hormonal contraceptive. The majority evolved for spontaneous cure. The time of accompaniment of the patients was around 6 and 12 months. In the stude of the patients with TTG it was only significant in the present of pregnance first and pregnance second patients, never parity and that it had never aborted, whose origin of the TTG was molar pregnance. The age bigger incidence of TTG was enters the 16 – 25 years. The stage most common was stage I. The more frequent small form of metastasis was the lung. The chemotherapywas efficient as only treatment in the majority of the cases. The gestations after TTG, had after occurred in its majority between 6 months and 2 years the treatmen. How much to the destination of the pregnancies, the majority evolved for normal gestation. The remission of the illness occurred in 90,5%. The time of accompaniment of the patients with TTG until the high one was equal or superior the 13 weeks.